Social Interaction of Children with Autism Reviewed From The Implementation of Diet Therapy in KB-TK Talenta Semarang - Rahayu, Siti; Handayani, Sri Sularti Dewanti (BELIA: Early Childhood Education Papers, 2018)
Autism is a neurological disorder that occurs due to birth defects and abnormalities that arise during the age of a toddler, abnormal development that is marked by disruption of communication, social interaction, and behavior. One effort to minimize the disorder that occurs in children with autism is therapy, one of them is diet therapy for autistic children. The diet that is often done in children with autism is GFCF (Gluten Free Casein Free). This study aims to explain the social interactions in autistic children who do diet therapy and those who do not take diet therapy at the Talenta KB-TK (Playgroup-Kindergarten) Semarang. This research uses the qualitative method. The main subject of this study is two autistic children who applied diet therapy and two autistic children who do not apply diet therapy. The data collection uses the method of observation, interviews, and documentation. The data is analyzed, and then the data is presented by drawing conclusions about the meaning of the data that has been collected. The results of this study indicate the difference of the social interaction of autistic children who apply the diet and who do not. The social interactions of autistic children who apply diet therapy at KB-TK Talenta Semarang are the existence of eye contact, flat facial expressions when invited to communicate, using body language when communicating, turning when called with voice or touch after several time yet no initiative to speak, joining friends yet no interaction, understanding the daily commands correctly. In the opposite, the social interactions of autistic children who do not apply the diet therapy are little eye contacts, flat face expression, using body language in communicating, inconsistent respond to a calling, one can speak while other only say few words, disengage with friends, understanding the commands yet not right.